Innovation systems of the Western Balkan Countries and regional cooperation needs in fostering innovation - Švarc, Jadranka (Array, 2012)
The paper aims to present the factors for fostering regional innovation cooperation and science-industry links in the Western Balkan Countries (WBC) which are identified by the survey based analysis of attitudes of researchers and entrepreneurs in the region. The comparison of the selected components of the innovation systems of the WBC are also briefly presented to illustrate their differences and similarities with a view of a carrying out a regional innovation strategy.